2010
DOI: 10.1073/pnas.1001249107
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the factors affecting the activation of alkane by Cp Rh(CO) 2 (Cp  = Cp or Cp*)

Abstract: Fast time-resolved infrared spectroscopic measurements have allowed precise determination of the rates of activation of alkanes by Cp′Rh(CO) (Cp 0 ¼ η 5 -C 5 H 5 or η 5 -C 5 Me 5 ). We have monitored the kinetics of C─H activation in solution at room temperature and determined how the change in rate of oxidative cleavage varies from methane to decane. The lifetime of CpRh(CO)(alkane) shows a nearly linear behavior with respect to the length of the alkane chain, whereas the related Cp*Rh(CO)(alkane) has clear o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 26 publications
(21 reference statements)
3
42
0
Order By: Relevance
“…A second aspect that has received significant attention is the intramolecular dynamic process, termed alkane chain walking in many metal‐alkane complexes . The use of 1 H NMR spectroscopy revealed a slow migration of the metal from one CH bond to another in the alkane by Ball and coworkers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second aspect that has received significant attention is the intramolecular dynamic process, termed alkane chain walking in many metal‐alkane complexes . The use of 1 H NMR spectroscopy revealed a slow migration of the metal from one CH bond to another in the alkane by Ball and coworkers .…”
Section: Introductionmentioning
confidence: 99%
“…The three aspects of metal‐alkane chemistry are intertwined as their energetics is comparable. Recently, George et al found that the primary CH activation is more favorable than the secondary CH activation in the d 8 complex [Cp′Rh(CO) (alkane)] (Cp ′ = η 5 ‐C 5 H 5 or η 5 ‐C 5 Me 5 ) . From kinetic simulation studies, they showed that the CH activations are slower than the exchange processes, and so the lifetimes of the complexes vary as the length of the alkane.…”
Section: Introductionmentioning
confidence: 99%
“…Hence protocols for interpreting free-energy profiles have been suggested, [20] and the value of kinetic simulations for understanding mechanisms is becoming increasingly recognized. [21] We use TST to predict rate constants based on the calculated activation free energies. Differences in free energy between stable species, also computed from the ab initio data (except for the equilibrium with 23 where we do not have CCSD(T) values and base our calculations on experiment [17] rather than the less accurate DFT value), are used to compute equilibrium constants.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…1.3‐migrations has also been found to be faster that 1,2‐migrations in the CH bond activation of a series of linear alkanes catalyzed by Cp'Rh(CO) 2 (Cp' = Cp or Cp*) by George, Hall and their coworkers employing the combination of high precision fast time‐resolved infrared (TRIR) spectroscopy and DFT calculations [39a] . They found that the lifetimes of Cp'Rh(CO)(alkane) always increase with chain lengths, but with a nearly linear behavior for CpRh(CO) and a more obvious oscillatory behavior for Cp*Rh(CO), as shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic and kinetic simulations based on density functional and coupled cluster calculations indicate an interplay between the rates of activation and migration that renders the different lifetimes, where the migrations along the alkane chain are more rapid than primary CH activations, which are less rapid in Cp*Rh(CO) than the CpRh(CO) counterpart, and the competition between migrations and primary CH activation controls the kinetics of the CH activations in the linear alkanes. Further investigations elucidating the balance between electronic and steric factors that tunes the alkane CH activation and migration reactivities are being undertaken in the same group [39b,c] …”
Section: Introductionmentioning
confidence: 99%